PENDETEKSIAN DIAGNOSA PENYAKIT KANDUNGAN PADA IBU HAMIL DENGAN MENGGUNAKAN METODE FORWARD CHAINING - Mulia Rahmayu (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2013)
Health problems of pregnant women is a national problem that needs to get top priority because it will determine the quality of human resources in future generations. Attention to the mother in a family need special attention because the Maternal Mortality Rate (MMR) in Indonesia is still very high. During pregnancy, maternal health conditions will determine whether or not the growth of a healthy fetus. But in fact, pregnancy itself can cause a decrease in maternal resistance which then triggered the emergence of some diseases. In this study an expert system application program by using the method of forwarding Chaining, to assist in the search for conclusions about the disease affecting pregnant women and prevention or solutions to overcome them without having to ask directly to the specialist.